MONETARY POLICY IN ORDER STABILIZE MACROECONOMICS - ISWANDIR ISWANDIR (JURNAL MITRA MANAJEMEN, 2013)
Abtract With monetary policy can attempt to control or direct the macro economy to the desired condition (better) to regulate the money supply. What is meant by better conditions are improving or maintaining outpit balance and price stability (control inflation). Through the government's monetary policy to maintain the ability to grow the economy, as well as to control inflation. If that does is add to the money supply, the government is said to take an expansionary monetary policy (expansive monetary). Meanwhile, if the money supply is reduced, then the command to take contractionary monetary policy (monetary contractive). Another term for contractionary monetary policy is tight monetary policy (tight money policy).